Estadio departamental del Meta (2020)
This degree project exalt the current use of the MACAL stadium, which is analyzed to find out the technical conditions of this building, evaluating its current state in front of the sports infrastructure regulation, its location, accessibility, mobility and security, characteristics that have not been resolved for all the sports activities that take place there. An example of this problems is the crowding of people during sports shows and the inactivity of this space in others seasons without any events. Therefore, the solution is an stadium that works in accordance with current FIFA regulations in a new location at the suburban area in the city of Villavicencio, considering the new architectural trends and technical requirements necessary for sports equipment of this magnitude; been articulate with an urban design that integrates and allows complementary activities, such as: others sports activities, recreation, contemplation tours and spaces and an alive commerce. Achieving a sports and social integration space that inspires a sense of belonging and allow the development of a healthy life around this unique and inspiring space.